The Study On The Acquisition Order Of English Morphemes In The First Semester Students In English Education Study Program At Bandar Lampung University - Yanuar Dwi Prastyo; Mirza Azhari (Universitas Bandar Lampung, 2011)
The aim of this research is to find out the order of morphemes acquisition in the first semester students at English Education Study Program, Teacher Training and Education Faculty, Bandar Lampung University. The subjects of this research are twenty-one students in the first semester at English study program at Bandar Lampung University. Their ages ranged from 17-35 years old. They studied English as a subject in their schools for more than 7 years. To obtain the research data, picture based story is used and the subjects of the research are asked to write a story based on the picture given. From their writings, the acquisition of five English morphemes is analyzed. The result shows that the order of morphemes acquisition on the subjects of the research are 1) Plural (90.4%), 2) Past regular (85.7%), 3) Progressive (83.8%), 4) Past irregular (82.7%) 5) Third person singular (50%).